Leitura e Produção de Textos em uma Perspectiva Dialógica: o Trabalho Com A notícia do Site Sensacionalista em Sala de Aula. - Sá, Juliane Nogueira de (2021)
This research is part of the Applied Linguistics line of research and comprises the elaboration and application of a didactic sequence, focusing on the news genre, in order to understand to what extent such a didactic-methodological strategy can contribute to the dialogical work with reading and textual production in basic education. Among the selected news, there are those published by the Sensacionalista website, which refer dialogically to previous texts and present singular characteristics, such as humor and irony. Some of the objectives of this work are: to expand the universe of news studied in the classroom, going beyond traditional news, as well as highlighting the need for the teacher/researcher in research aimed at the classroom; apply the didactic sequence in an elementary-level class of a public school; to develop a work of analysis and discussion about intertextuality, irony and humor, present, above all, in news on the Sensacionalista website, and to analyze the results of the didactic sequence through classroom episodes and students' textual productions. In this sense, this work is theoretically supported by the studies of Bakhtin and his Circle (1987; 1993; 2003; 2006; 2013); Dolz, Noverraz and Schneuwly (2004); Koch, Bentes and Cavalcante (2012); Brait (2005; 2008; 2013); Geraldi (2011; 2015); Lopes-Rossi (2011); Rojo (2005; 2013; 2015), among others. The corpora is composed of the description and analysis of the interactions between the teacher/researcher and the students during the application of the didactic sequence in the classroom and five news items, produced by students from a 7th grade elementary school class at a public school located in Serra/ES. From the analysis of the news, considering the initial production, the aspects related to the classroom episodes that occurred during the application of the didactic sequence and the final production of the news, the results allow us to corroborate that, through the bias of intertextuality and others resources used by the site, such as humor and irony, in a dialogical perspective, it is possible to develop the critical reflection of students who, in the production of texts, say a lot about the place where they live.